Anthelmintic activity of Ethanolic extract of whole plant of Eupatorium Odoratum. L - Jitendra Patel; G.S. Kumar; Md. Shamim Quresh; P.K. Jena (International Journal of Phytomedicine, 2010)
Successive extracts from the Whole plant of Eupatorium Odoratum. L (Asteraceae) were investigated for their anthelmintic activity against Pheretima posthuma and three concentrations (10, 50 and 100 mg/ml) of each extracts were studied in activity, which involved the determination of time of paralysis and time of death of the worm. Ethanolic extract exhibited significant anthelmintic activity at highest concentration of 100 mg/ml. Piperazine citrate in 10 mg/ml concentration as that of extract was included as standard reference and 1% Gum acacia in normal saline as control. The anthelmintic activity of ethanloic extract was significant followed by hydroalcoholic extract of Eupatorium Odoratum.